On the hydrogeothermal structure of the Figuig region (eastern High Atlas, Morocco) - Jilali, Abdelhakim (2016)
This study is to analyze the tectonic, hydrogeological and geothermal circumstances that are causing the upwelling of the thermal springs in the Figuig region whose temperatures range from 27 to 34 °C. From the north, the groundwater flow in carbonated formations is channeled to the oasis of Figuig. These groundwaters emerge thanks to faults under conditions of geothermal gradients and heat flow density ranging from 22 to 35 °C/km and 58-95 mW/m2 respectively.